Age stratified, matched comparison of unicompartmental and total knee replacement - Kennedy, J; Mohammad, H; Mellon, S; Dodd, C; Murray, D (Elsevier, 2020)
Background: Unicompartmental knee replacement (UKR) tends to provide better function but has a higher revision rate than total knee replacement (TKR). The aim was to determine if this occurred in all age groups.